How the Religious Right Shaped Lesbian and Gay Activism - Fetner, Tina (Book collections on Project MUSE., 2008)
While gay rights are on the national agenda now, activists have spent decades fighting for their platform, seeing themselves as David against the religious right's Goliath. At the same time, the religious right has continuously and effectively countered the endeavors of lesbian and gay activists, working to repeal many of the laws prohibiting discrimination based on sexual orientation and to progress a constitutional amendment "protecting" marriage. In this accessible and grounded work, Tina Fetner uncovers a remarkably complex relationship between the two movements--one that transcends politic